Ефективність релейного захисту місцевих ліній - Карпалюк, Ігор Тимофійович; Баженов, Володимир Миколайович; Одєгов, Микола Миколайович; Горюн, Олег Олегович; Karpaliuk, Ihor; Bajenov, Volodymyr; Odiehov, Mykola; Horiun, Oleg (Запоріжжя : ТДАТУ, Видавничий дім «Гельветика», 2025)
UA: У роботі розглянуто особливості функціонування релейного захисту високовольтних ліній 110–220 кВ в умовах дефіциту генеруючої потужності та струму короткого замикання, що характерне для автономних локальних енергосистем у періоди надзвичайних ситуацій, зокрема у воєнний час. Проведено аналіз умов спрацювання резервних струмових та дистанційних захистів ліній у нестандартних режимах роботи енергосистеми. Запропоновано рекомендації щодо вибору уставок, забезпечення селективності, чутливості та надійності спрацювання захистів за мінливих потоків потужності. Установлено, що ефективність резервного захисту суттєво знижується зі зменшенням потужності системи, особливо за живлення з боку слабких джерел. Обґрунтовано доцільність застосування додаткових захисних заходів, таких як селективна струмова відсічка з витримкою часу та використання АПВ із блокуванням. EN: The paper investigates the specific features of relay protection operation for high-voltage power transmission lines rated at 110–220 kV under conditions of limited generation capacity and reduced short-circuit current levels. Such conditions typically arise in autonomous or isolated local power systems operating during emergencies, particularly in wartime or following major accidents that result in the loss of connection with the main power grid. The study analyzes the impact of non-standard operating modes on the performance of backup overcurrent and distance protection schemes, identifying potential errors in relay behavior under weak infeed conditions. Examples of selectivity violations, sensitivity loss, and reduced reliability of protection devices due to significantly lower fault currents are presented. It is shown that traditional protection settings and coordination methods do not ensure effective operation in isolated system scenarios. Approaches to improve the settings of overcurrent and distance protection are proposed, taking into account the reduced capacity of power supply sources. The paper discusses the feasibility of implementing additional technical solutions such as time-delayed selective overcurrent protection, adaptive auto-reclosing blocking, and the use of information from automated control systems to enhance protection performance. The results of this study can be applied in the design, modernization, and operation of relay protection systems in local power networks.
Efficiency of relay protection for local power transmission lines
Keywords: релейний захист; дефіцит потужності; слабкі джерела живлення; ефективність резервного захисту; чутливість захисту; надійність спрацювання; максимальна струмова відсічка; селективна струмова відсічка; автоматичне повторне включення; relay protection; power deficit; weak power sources; efficiency of backup protection; protection sensitivity; operating reliability; instantaneous overcurrent protection; selective overcurrent protection; automatic reclosing